Ukuran Direksi, Kepemilikan Institusional, dan Kebijakan Dividen terhadap Kinerja Keuangan - Riswell Afrindo Manurung; Amin Wijoyo (Jurnal Multidisiplin Indonesia, 2026)
This study aims to examine the influence of the size of directors, institutional ownership, and dividend policy on financial performance proxied by Return on Equity (ROE) in LQ45 index companies on the Indonesia Stock Exchange for the 2021–2024 period. Based on Agency Theory and Signaling Theory, this study emphasizes the role of corporate governance mechanisms in mitigating agency conflicts and increasing profitability. Panel data from 21 companies (84 observations) were analyzed using the Fixed Effect Model. The results of the partial analysis showed that the size of the board of directors (β = −0.006; p = 0.944), institutional ownership (β = 0.404; p = 0.132), and dividend policy (β = −0.017; p = 0.270) had no significant effect on ROE. However, overall the Fixed Effect model is significant with an F-statistic of 16.679 and an Adjusted R² of 81.29%. These findings indicate that ROE variation is explained more by company-specific characteristics than by the governance variables tested. This research provides an empirical contribution that the effectiveness of governance is not always reflected in short-term financial indicators, but is influenced by more complex internal factors of the company. The practical implications underscore the need for companies to strengthen their managerial strategies and internal policies to improve financial performance in a sustainable manner.